Aspectos biológicos, morfometria e técnica de criação de Abaris basistriata Chaudoir, 1873 e Selenophorus seriatoporus Putzeys, 1878 (Coleoptera: carabidae) - Andrade, Crislany de Lima Barbosa [UNESP] (2014)
The family Carabidae (Coleoptera) is recognized worldwide as containing important species of biological control agents of agricultural pests. Our aim was to study the biology, morphometrics and rearing protocol of Abaris basistriata Chaudoir, 1873 (Harpalinae: Pterostichini) and Selenophorus seriatoporus Putzeys, 1878 (Harpalinae: Harpalini) using Tenebrio molitor Linnaeus, 1758 (Coleoptera: Tenebrionidae: Tenebrioninae: Tenebrionini) larvae as the diet. The study was conducted in environmental chambers at 26±1°C, 70±10% relative humidity, under a photoperiod of 14:10h (L:D). Containers used to egg laying and rearing larvae, pupae, and adults, were filled with one of the following types of sterilized and moistened substrate: (1) soil, (2) fine vermiculite, or (3) paper napkins. The life cycle (egg to adult) of A. basistriata and S. seriatoporus showed differences in duration in soil and paper substrates. The viability of eggs and larvae of first and second instars was similar in the three substrates studied, while the third instar and pupae in the soil showed improved survival when compared with vermiculite and paper. The soil substrate was more favorable to the longevity of A. basistriata, and the females live longer than males, while in S. seriatoporus this biological parameter was similar. Abaris basistriata showed lower pre-oviposition period and higher oviposition and post-oviposition on soil. Also, fecundity and viability of A. basistriata were higher when created in the container with respect to the soil or vermiculite and paper. The T. molitor larvae were adequate to keep creating A. basistriata and S. seriatoporus in the laboratory. The moisture conditions of subtrato interfere in larval survival of carabid. The soil was the substrate that provided better conditions for the complete life cycle of A. basistriata and S. seriatoporus, however the vermiculite and paper were easy to handle substrates that made possible the ...